2013
DOI: 10.3171/2013.5.jns1311
|View full text |Cite
|
Sign up to set email alerts
|

A practical grading scale for predicting outcome after radiosurgery for arteriovenous malformations: analysis of 1012 treated patients

Abstract: Object. The authors performed a study to review outcomes following Gamma Knife radiosurgery for cerebral arteriovenous malformations (AVMs) and to create a practical scale to predict long-term outcome.Methods. Outcomes were reviewed in 1012 patients who were followed up for more than 2 years. Favorable outcome was defined as AVM obliteration and no posttreatment hemorrhage or permanent, symptomatic, radiationinduced complication. Preradiosurgery patient and AVM characteristics predictive of outcome in multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
150
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(158 citation statements)
references
References 40 publications
5
150
2
1
Order By: Relevance
“…Moreover, deep AVM are reported to have lower obliteration rates after radiosurgery [10,[25][26][27]. Hattangadi-Gluth et al [10] reported an obliteration rate of 62% in AVM located in deep structures.…”
Section: Discussion Implicationsmentioning
confidence: 99%
“…Moreover, deep AVM are reported to have lower obliteration rates after radiosurgery [10,[25][26][27]. Hattangadi-Gluth et al [10] reported an obliteration rate of 62% in AVM located in deep structures.…”
Section: Discussion Implicationsmentioning
confidence: 99%
“…Patients with small AVMs (P=0.035) located in noneloquent brain regions (P=0.023) were more likely have a favorable outcome, which is consistent with previous AVM radiosurgery series. 9,15,16 With radiosurgery, the vast majority of complications associated with the treatment of ARUBA-eligible patients occurred within the first 2 years. Thereafter, the benefits of radiosurgery became more apparent over time, especially after the typical 3-year latency period after radiosurgery ( Figure 2B).…”
Section: February 2016mentioning
confidence: 99%
“…[14][15][16] The radiosurgery technique used at each institution has been previously described. 17 Briefly, a Leksell Model G stereotactic frame (Elekta AB, Stockholm, Sweden) was affixed to the calvarium after administration of local anesthesia.…”
Section: Baseline Data and Variablesmentioning
confidence: 99%
“…Stereotactic radiosurgery has gained popularity in recent years. 1,2,4,5,[7][8][9][10][11][12]21 Its effect on the obliteration of AVMs is gradual, with patients remaining at risk for hemorrhage during this latency period. Complete obliteration, after a single session, has been reported to vary between 60% and 80% over 5 years.…”
mentioning
confidence: 99%
“…Complete obliteration, after a single session, has been reported to vary between 60% and 80% over 5 years. 1,2,4,5,7,21 Several metrics have been used to determine the appropriate prescribed dose during SRS for AVMs. One of the most widespread methods utilizes the K index, 14 first introduced in 1997 by Karrlson et al at the Karolinska Institute, Sweden.…”
mentioning
confidence: 99%